Determination of tourism activities of the world’s best tourism destinations using the multi-criteria decision-making method - Ilban, Mehmet Oğuzhan (Cogent social sciences, 2017)
In this study, the tourism performance of the 15 countries that are the most popular global tourist destinations are analyzed using the TOPSIS method. Four factors are employed to measure the tourism activities in these countries: international tourism expenditures, international tourism receipts, number of international tourism arrivals and number of international tourism departures. The TOPSIS method is applied to combine the four factors and convert them into a single performance score. The countries are then ranked and rated. Tourism activities are used to grade the countries’ performance scores. In this way, the valuation of tourism activities in the 15 countries is determined for the 6 years between 2009 and 2014. The results are compared with the results of international tourism organizations.